Four fish : the future of the last wild food - Greenberg, Paul, 1967- (Penguin Press, 2010)
"Award-winning writer and lifelong fisherman Paul Greenberg takes us on a culinary journey, exploring the history of the fish that dominate our menus -- salmon, sea bass, cod, and tuna -- and investigating where each stands at this critical moment in time"--Dust jacket.